Pengembangan Student Worksheets Berbasis Discovery Learning Melalui Lesson Study Materi Program Linear - Wahyudi Wahyudi; Sabekti Trinuryono; Muji Herini; Nurul Hidayati; Sumarno Sumarno (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
So far, the probing method used to solve linear programming problems has not become an alternative method. Students often find the corner point test method easier to solve linear programming problems. The purpose of this research is to produce student worksheets based on discovery learning of linear programming material for class XI SMA. This research is a research and development (research and development). The test subjects in this study were 18 students of SMAN 1 Babadan Ponorogo. The results of the feasibility assessment obtained valid and appropriate categories by material experts with an average total score of 3.35 and the value of media experts was 2.61. Thus, it can be concluded that student worksheets can be used as teaching materials and are able to improve students' abilities in solving problems related to linear programming material.